Synthesis of silk fibroin-glycopolypeptide conjugates and their recognition with lectin - Das, Soumen; Pati, Debasis; Tiwari, Neha; Nisal, Anuya; Sen Gupta, Sayam (Biomacromolecules, 2012)
Silk fibroin (SF), the natural fibrous protein created by the Bombyx mori silk worm, is being increasingly excellent mechanical strength, high oxygen/water permeability, excellent mechanical strength; high oxygen/water:permeability, and biocompatibility: :It is also well known that surface. modification of SF, With Organic ligands such as the extracellular protein :binding. Arg-Gly-Asp, (RGD) peptides:,: help adhesion and,proliferation. of cells better-a key; requirement for it to function as extracellular. matrices; In this, Work, We have conjugated synthetic glycopolypeptides (GPs) that were synthesized by controlled ring opening polymerization of alpha-manno-lys N-carboxyanhydrides (NCAs) onto SF by using Cu catalyzed click reaction to synthesize 1 a new hybrid :Material (SF GP), Which We believe will have :both the mechanical properties of native SF and the molecular recognition property of the carbohydrates in the GP. By controlling the :amount of GP grafted onto SF, we have made three SF GP conjugates that differ in their ability to assemble into films. SF GP conjugates having a very high content of GP formed completely water soluble brush like polymer that displayed very high affinity toward the lectin concanavalin-A (Con-A) Films cast from SF-GP conjugates using lower amounts of grafted GP were more stable in water, and the stability can be modulated by varying the amount of G grafted. The water insoluble film SF-GP(25) was also found to bind to fluorescently labeled Con A, as was seen by confocal microscopy Such SF-GP hybrid films may be useful as mimics of extracellular matrices for tissue engineering: